COVIC: Collecting Visualizations of COVID-19 to Outline a Space of Possibilities. - Kahn, Paul; Dubberly, Hugh; Rodighiero, Dario (Design Issues)
We describe the COVID-19 Online Visualization Collection (COVIC), its goals, how it came to be, and why we propose such a collection as a new path for design research. The COVIC database contains a collective visualization response to the COVID-19 pandemic gathered from approximately 3,000 articles, each containing one or more visualizations (about 12,000 in total). We have sought to create a resource for design research—a boundary object—that will be useful to any of the disciplines brought together through their response to the pandemic event.